Extraperitoneal laparoscopy for para-aortic lymphadenectomy in endometrial carcinoma staging: an approach with higher efficiency - Wei Zhang (BMC, 2021)
Abstract Background Removing more inframesenteric nodes is not only significantly increases the likelihood of finding metastasis for endometrial cancer, but also can add survival advantage. As most patients diagnosed with endometrial cancer are overweight or obesity, a high efficiency approach is important. Aim of this study was to compare the surgical outcomes of extraperitoneal laparoscopic, transperitoneal laparoscopic, and laparotomic para-aortic lymphadenectomy in endometrial carcinoma staging. Methods We retrospectively reviewed data of all patients diagnosed with primary endometrial carcinoma who were treated at the Department of Gynecologic Oncology, Fudan University Shanghai Cancer Center from 1 January 2017 to 31 December 2019. The numbers of para-aortic lymph nodes, surgical time, complications, blood loss and hospital stay were compared. The patients’ medical records and pathological reports were carefully reviewed. Statistical significance was defined as p < 0.05. Results We retrospectively compared patients who underwent extraperitoneal laparoscopy (Group E, n = 20), transperitoneal laparoscopy (group T, n = 21), and laparotomy (group L, n = 135). The median number of para-aortic lymph nodes was significantly higher in group E than in groups T and L (9.5, 5, and 6, respectively; p = 0.004 and 0.0004, respectively). All patients in group E underwent successfully dissection to the renal vessel level. The median operation time was significantly shorter in group L than in groups T and E (94, 174, and 233 min, respectively; p < 0.0001). The median estimated blood loss volume was higher in group L than in groups T and E (200, 100, and 142.5 ml, respectively; all comparisons p < 0.001), and the length of hospital stay was significantly longer in group L than in Groups T and E (6, 5, and 6 days, respectively; all comparisons p < 0.001). Conclusion The extraperitoneal laparoscopic approach for staging endometrial carcinoma harvested higher numbers of para-aortic lymph nodes which could be considered for endometrial carcinoma staging, especially for para-aortic lymph node harvest.